United States : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
Focus. The 2014 Article IV Consultation focused on five broad themes to strengthen the recovery and improve the long-term outlook: raising productivity growth and labor force participation, confronting poverty, keeping public debt on a sustained downward path, smoothly managing the exit from zero policy rates, and securing a safer financial system. Main policy issues. -- Policies are needed to boost longer-term potential output through investments in infrastructure, raising educational outcomes, improving the tax structure, and developing and expanding a skilled labor force (including through immigration reform, job training, and providing childcare assistance for working families). -- Forging agreement on a credible, medium-term consolidation plan should be a high priority and include steps to lower the growth of health care costs, reform social security, and increase revenues. In the absence of such a comprehensive agreement, efforts should still focus on identifying more modest opportunities to relax the near- term budget envelope, paid for with future fiscal savings. -- An enduring consequence of the past recession has been a jump in the number of families living in poverty. Improved employment prospects and economic growth will be essential to reverse this upward movement. An expansion of the Earned Income Tax Credit and an increase in the minimum wage should also be part of the solution. -- The goal for monetary policy is to manage the exit from zero interest rates in a manner that allows the economy to converge to full employment with stable prices while avoiding financial instability and negative spillovers to the global economy. This is a complex undertaking. To facilitate it, steps could be taken to expand the Fed's communications toolkit so as to provide greater clarity on how the Federal Open Market Committee assesses progress toward its longer-run goals. -- Continued regulatory oversight is needed to counter the emergence of financial imbalances, particularly those that may be growing outside of the banking system. Policies should also be deployed to keep mortgage credit accessible and attract more private capital into housing finance while minimizing risks to taxpayers. -- The U.S. external position is assessed to be broadly consistent with medium-term fundamentals and desirable policies.